Comprehension competence: personal attitudes’ effect on the intentions to read critically in a foreign language - Migena Alimehmeti; Irena Shehu (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study explores the relationship between personal attitudes and the intention to engage in critical reading among students learning a foreign language. Grounded in theories of motivation, cognition, and critical pedagogy, the research aims to determine whether favorable attitudes influence students’ willingness to read critically. A quantitative approach was employed, using a structured questionnaire administered to a purposive sample of 200 undergraduate students at the Faculty of Foreign Languages, University of Tirana. The instrument measured two key constructs: personal attitudes and intentions to read critically, through Likert-scale items. Reliability and validity were confirmed via Cronbach’s alpha (.855 and .920) and factor analysis (Kaiser-Meyer-Olkin (KMO)=.885). Data were analyzed using SPSS, including descriptive statistics and Pearson correlation. Results revealed a statistically significant and moderately strong positive correlation between personal attitudes and critical reading intentions (r=.645, p<.01), suggesting that students who hold more favorable views toward critical reading are more likely to intend to engage in it. Despite overall positive attitudes, the intentions to pursue critical reading beyond academic settings were only moderate, indicating potential barriers or a lack of long-term motivation. The study highlights the need for pedagogical strategies that enhance students’ appreciation for critical reading, as fostering positive attitudes may lead to greater engagement and skill development in this essential area. The study concludes with pedagogical recommendations for fostering positive attitudes to enhance engagement in critical reading.